2006
DOI: 10.1016/j.ijpsycho.2005.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-to-heavy alcohol intake is associated with differences in synchronization of brain activity during rest and mental rehearsal

Abstract: In alcohol-dependent individuals, synchronization of brain activity is different from that in non-alcohol-dependent individuals as reflected by EEG differences at alpha and beta frequencies . These EEG differences may not only be related to long-term alcohol intake but also to genetic factors that are associated with alcohol dependence. Thus, it is not known what the pure effect of long-term alcohol intake on synchronization of brain activity is. Therefore, we investigated whether EEG synchronization differs b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 83 publications
5
24
0
Order By: Relevance
“…Importantly, adolescents with alcohol use disorders demonstrate functional brain abnormalities [87], and even moderate alcohol use may impact neural functioning [88]. Yet the inclusion of marijuana users with other substance use histories maintains representativeness in the sample, allowing for better generalization to the population of adolescent marijuana users.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, adolescents with alcohol use disorders demonstrate functional brain abnormalities [87], and even moderate alcohol use may impact neural functioning [88]. Yet the inclusion of marijuana users with other substance use histories maintains representativeness in the sample, allowing for better generalization to the population of adolescent marijuana users.…”
Section: Discussionmentioning
confidence: 99%
“…A high level of coherence between two EEG signals indicates a coactivation of neuronal populations and provides information on functional coupling between these areas (Franken, Stam, Hendriks, & van den Brink, 2004). De Bruin et al (2004) and De Bruin, Stam, Bijl, Verbaten, and Kenemans (2006 investigated the pure effects of alcohol intake on synchronization of brain activity while minimizing the confounding influence of genetic factors related to alcohol dependence. They showed that heavily drinking students with a negative family history had stronger EEG synchronization at theta and gamma frequencies than lightly drinking students with a negative family history.…”
Section: Qeeg In Sudmentioning
confidence: 99%
“…Winterer, Enoch, et al (2003) and Winterer, Smolka, et al (2003) described higher left-temporal alpha and slow-beta coherence and higher slowbeta coherence at right-temporal and frontal electrode pairs in alcohol-dependent male and female participants. De Bruin et al (2006) showed that moderate to heavy alcohol consumption is associated with differences in synchronization of brain activity during rest and mental rehearsal. Heavy drinkers displayed a loss of hemispheric asymmetry of EEG synchronization in the alpha and slow-beta band.…”
Section: Qeeg In Sudmentioning
confidence: 99%
“…The fact that alcoholics have cognitive deficits in performing complex coordinated tasks suggests some related differentiation in brain functional connectivity as expressed by synchronization between different neural assemblies [2]. Synchronous oscillations of certain types of such assemblies in different frequency bands captured by both linear and nonlinear methods have been successfully used in the past as indices of cerebral engagement in cognitive tasks or brain pathologies [3].…”
Section: Introductionmentioning
confidence: 99%